Pelatihan Memasak Mie Sehat Gluten Free di Komunitas Health Food YLBS Jember - Raadliyatush Shalihah; Muhammad Habibi Hamzah (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity was conducted at Yayasan Lansia Bahagia Sejahtera, which hosts the Healthy Food community, consisting mostly of elderly members. The training aimed to teach participants how to cook healthy gluten-free noodles as an effort to promote better health. The activity was carried out through several stages, beginning with participant registration and the distribution of recipes, followed by an explanation of the theory and ingredients used. The session then continued with hands-on practice, accompanied by a question-and-answer session to ensure that participants could understand each step of the cooking process. An evaluation process was also conducted after the training by assessing the participants’ practical results at home.